Safety and efficacy of tirofiban after early neurological deterioration in patients with branch atheromatous disease receiving alteplase - Zhong, Xuemin; Zhao, Meng; Xu, Ronghua; Wang, Jian; Du, Jiaxiu (Frontiers in Stroke, 2022)
Objectives No standard treatment exists for branch atheromatous disease (BAD), and patients' conditions often worsen after thrombolytic therapy. We evaluated the safety and effectiveness of tirofiban after early neurological deterioration (END) development in patients receiving intravenous alteplase. Materials and methods Bleeding incidence, National Institute of Health Stroke Scale (NIHSS) score, and modified Rankin scale (mRS) score were assessed for patients with BAD receiving alteplase within 4.5 h of stroke onset. Results Among 193 patients, 119 (61.64%) did not experience exacerbation after thrombolytic treatment, 74 (38.34%) had END, 34 were treated with tirofiban after END, and 40 received standard treatment. On day 7 or at discharge, no cases of symptomatic cerebral hemorrhage were noted, and no patient died during the 90-day follow-up. Fifty-two of 74 patients (70.27%) had a good mRS score at 90 days. Among patients with END who received tirofiban, 27 (79.41%) had a good mRS score at 90 days, which was significantly better than that of the 18 cases that did not receive tirofiban after exacerbation (45%; P < 0.001). NIHSS scores were significantly lower 24 h, 48 h, and 7 days after tirofiban treatment in patients with exacerbation after thrombolytic therapy than in those without tirofiban treatment. Conclusions Patients with BAD have elevated risks of END after thrombolytic therapy. Compared with conventional oral antiplatelet aggregation drugs, tirofiban rescue therapy resulted in significantly better NIHSS and mRS scores without increased symptomatic cerebral hemorrhage rates.